2021
DOI: 10.1002/jae.2859
|View full text |Cite
|
Sign up to set email alerts
|

News media versus FRED‐MD for macroeconomic forecasting

Abstract: Using a unique dataset of 22.5 million news articles from the Dow Jones Newswires Archive, we perform an in depth real-time out-of-sample forecasting comparison study with one of the most widely used data sets in the newer forecasting literature, namely the FRED-MD dataset. Focusing on U.S. GDP, consumption and investment growth, our results suggest that the news data contains information not captured by the hard economic indicators, and that the news-based data are particularly informative for forecasting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 68 publications
1
13
1
Order By: Relevance
“…A value less than 1 in the relative RMSE score indicates that the textaugmented forecast has a lower RMSE relative to the mean of the PF. Unlike the findings based on US data (Bianchi et al, 2022;Ellingsen et al, 2021), all four text-augmented predictions for GDP growth rate outperform the PF in our exercise. The differences in predictive performance are also statistically significant according to the DM test.…”
Section: Comparison With the Professional Forecastcontrasting
confidence: 99%
See 3 more Smart Citations
“…A value less than 1 in the relative RMSE score indicates that the textaugmented forecast has a lower RMSE relative to the mean of the PF. Unlike the findings based on US data (Bianchi et al, 2022;Ellingsen et al, 2021), all four text-augmented predictions for GDP growth rate outperform the PF in our exercise. The differences in predictive performance are also statistically significant according to the DM test.…”
Section: Comparison With the Professional Forecastcontrasting
confidence: 99%
“…More concretely, we apply HDMR to construct the text‐based predictors from the PBC communication texts and then embed them into a MIDAS‐type model that can learn from mixed‐frequency macro and textual data, as well as produce the forecast to the target of interest. Accordingly, our results are related to the recent forecasting literature that uses text as data, for example, Kelly et al (2021) and Ellingsen et al (2021). In contrast, our work extends these applications by studying an entirely different corpus, central bank communication texts.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Here, we assess algorithms that do not learn (for instance, dictionary and Boolean methods) as well as supervised machine learning as our sample size is large enough for it to be effective in forecasting the (continuous) economic variables that most concern policymakers. More recently, Ellingsen et al (2021) have shown that news text data contain information not captured by hard economic indicators, including information that is particularly useful in forecasting consumption.…”
Section: Introductionmentioning
confidence: 99%